Capital and development planning - Chakravarty, Sukhamoy (Cambridge, Mass.: M.I.T. Press, 1969)
This book is on area of construction of planning models that may help the responsible political authority in many underdeveloped economies.
Include index
Bibliography: p. [329]-340.
oo 14/09/18
Loans
Keywords: Economic policy